How to-- make a million - "Morgan, Rowland" (Oxford University Press: Oxford, 2001)
A money guide - what it is, how it has changed over the centuries, and different ways to create, save, or spend money. It shows children the richest people ever, why a GBP50 note costs only 3 pence, and where you can find a million-pound note. It looks at ways that people could have made a million in the past.
Keywords: Wealth Juvenile-literature